2014
DOI: 10.1515/hsz-2013-0290
|View full text |Cite
|
Sign up to set email alerts
|

The extended reductive acetyl-CoA pathway: ATPases in metal cluster maturation and reductive activation

Abstract: The reductive acetyl-coenzyme A (acetyl-CoA) pathway, also known as the Wood-Ljungdahl pathway, allows reduction and condensation of two molecules of carbon dioxide (CO2) to build the acetyl-group of acetyl-CoA. Productive utilization of CO2 relies on a set of oxygen sensitive metalloenzymes exploiting the metal organic chemistry of nickel and cobalt to synthesize acetyl-CoA from activated one-carbon compounds. In addition to the central catalysts, CO dehydrogenase and acetyl-CoA synthase, ATPases are needed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 92 publications
(144 reference statements)
0
11
0
1
Order By: Relevance
“…Previous studies have shown that integration of nickel into the C-cluster is dependent on the accessory protein CooC (15)(16)(17). Certain organisms express additional proteins, CooJ and CooT, that have been implicated in C-cluster maturation; however, CooC appears to be the only dedicated and essential maturation factor expressed by all CODH-containing organisms (15,(18)(19)(20)(21)(22). CooC is a P-loop ATPase with sequence similarity to UreG and HypB, maturation factors involved in nickel transfer to the active sites of urease and Ni-Fe hydrogenase, respectively (15,23).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that integration of nickel into the C-cluster is dependent on the accessory protein CooC (15)(16)(17). Certain organisms express additional proteins, CooJ and CooT, that have been implicated in C-cluster maturation; however, CooC appears to be the only dedicated and essential maturation factor expressed by all CODH-containing organisms (15,(18)(19)(20)(21)(22). CooC is a P-loop ATPase with sequence similarity to UreG and HypB, maturation factors involved in nickel transfer to the active sites of urease and Ni-Fe hydrogenase, respectively (15,23).…”
Section: Introductionmentioning
confidence: 99%
“…Several biological carbon dioxide (CO 2 ) to biomass conversion pathways exist in prokaryotes and eukaryotes [ 8 ]. Various prokaryotes employ the Wood-Ljungdahl pathway to reductively form acetyl coenzyme-A [ 9 , 10 ]. Carbon monoxide (CO) as obtained from CO 2 reduction by CO dehydrogenase (CODH) is utilized in a reaction involving two enzymes, corrinoid iron-sulfur protein (CoFeSP) with a methyl group bound to the cobalt ion of its cobalamin cofactor and acetyl-CoA synthase (ACS), to produce acetyl-CoA, the central metabolic building block ( Eq 1 ) [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cbl is essential for all mammals [ 5 ] and in bacteria it is involved in carbon oxide (CO x ) conversion pathways related to potential renewable energy applications [ 6 , 7 ]. Anaerobic CO 2 reduction along the bacterial Wood-Ljungdahl pathway includes several unique enzymes [ 8 , 9 ]. The corrinoid iron-sulfur protein (CoFeSP) carries a Cbl cofactor [ 10 , 11 ] and shuttles a methyl group from methyl-transferase bound methyl-tetrahydrofolate to acetyl-CoA synthase.…”
Section: Introductionmentioning
confidence: 99%